An unusual case of acute pulmonary embolism - Nicolaou, N.; Conradie, D.C.; Bloy, B.; Richards, G.A. (SA Heart Journal, 2017)
Patiant with a history of hypertension presented to the emergency room with progressive dyspnoea over afew weeks. There was no relevant past history. Clinical examination revealed an elevated jugular venous pressure, pedal oedema and tenderness in the right hypochondrium.